The role of river drainages in shaping the genetic structure of capybara populations - Byrne, María Soledad (2015)
The capybara, Hydrochoerus hydrochaeris, is an herbivorous rodent widely distributed throughout most of South American wetlands that lives closely associated with aquatic environments. In this work, we studied the genetic structure of the capybara throughout part of its geographic range in Argentina using a DNA fragment of the mitochondrial control region. Haplotypes obtained were compared with those available for populations from Paraguay and Venezuela. We found 22 haplotypes in 303 individuals. Hierarchical AMOVAs were performed to evaluate the role of river drainages in shaping the genetic structure of capybara populations at the regional and basin scales. In addition, two landscape genetic models, isolation by distance and isolation by resistance, were used to test whether genetic distance was associated with Euclidean distance (i.e. isolation by distance) or river corridor distance (i.e. isolation by resistance) at the basin scale. At the regional scale, the results of the AMOVA grouping populations by mayor river basins showed significant differences between them. At the basin scale, we also found significant differences between sub-basins in Paraguay, together with a significant correlation between genetic and river corridor distance. For Argentina and Venezuela, results were not significant. These results suggest that in Paraguay, the current genetic structure of capybaras is associated with the lack of dispersion corridors through permanent rivers. In contrast, limited structuring in Argentina and Venezuela is likely the result of periodic flooding facilitating dispersion.